2010
DOI: 10.1128/aac.01398-09
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis of Multidrug Resistance in Acinetobacter Clinical Isolates in Taiwan

Abstract: Multidrug-resistant (MDR)Acinetobacter

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 40 publications
2
30
1
Order By: Relevance
“…This was unlikely, as transformation of a plasmid harboring only the ISAba1-bla OXA-51 -like gene (ISAba1-bla OXA-82 ) was enough to confer a high level of carbapenem resistance. This phenomenon has also been recently demonstrated (16). Interestingly, the N-type isolates also had a higher sulbactam resistance rate, the mechanism of which is undetermined.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This was unlikely, as transformation of a plasmid harboring only the ISAba1-bla OXA-51 -like gene (ISAba1-bla OXA-82 ) was enough to confer a high level of carbapenem resistance. This phenomenon has also been recently demonstrated (16). Interestingly, the N-type isolates also had a higher sulbactam resistance rate, the mechanism of which is undetermined.…”
Section: Discussionsupporting
confidence: 63%
“…For example, ISAba1 upstream of the bla OXA-51 -like gene is associated with the overexpression of the bla OXA-51 -like gene and carbapenem resistance in A. baumannii (12,23). However, some isolates harboring the bla OXA-51 -like gene with an upstream ISAba1 (ISAba1-bla OXA-51 -like gene) are still susceptible to carbapenem (9,14,16). The reason for this discrepancy in carbapenem susceptibility levels in isolates harboring the ISAba1-bla OXA-51 -like gene has not been completely clarified.…”
mentioning
confidence: 99%
“…However, the distribution of gene cassettes in our study differed from that found in food samples in other countries such as Tunisia and Norway, where dfrA1-aadA1 was the dominant array [17,18]. The cassette array aacA4-catB8-aadA1, encoding tobramycin, chloramphenicol, and streptomycin resistance, respectively, has been found frequently in Acinetobacter isolates in many previous studies [19,20,21]. To our knowledge, aacA4-catB8-aadA1 was not common among E. coli isolates [22,23].…”
Section: Discussioncontrasting
confidence: 88%
“…These results are similar to those in our report. However, a report from another medical center in northern Taiwan revealed that only 3.4% of CRAB isolates harbored the bla OXA-23 -like gene (11). Reports from 2 hospitals in central Taiwan showed a higher occurrence of the bla OXA-23 -like gene (93% and 96%, respectively) (12,13).…”
Section: Discussionmentioning
confidence: 98%